The covenant in the Holy Quran -An objective study- (Journal of the College of Basic Education, 2022)
The covenant is that the commissioner, God Almighty, pledges to do or leave something, which is an agreement that a Muslim makes with any other party (a Muslim or an infidel). God has commanded the fulfillment of the covenant, and the Islamic religion stressed the need to abide by it, as it forbids treachery and ugliness. And the fulfillment of the covenant, which is required by the noble character, and is required by the generosity of the soul. The word covenant came in the Noble Qur’an in several verses and several surahs, and here you realize the great importance of that meaning. The word covenant also appeared in authentic hadiths in which the word covenant was pronounced and others in which the covenant was pronounced, and this gives a sure indication of the importance of the covenant and the extent of its care. The word covenant was used in several areas, and it came to decide that great ideas.